In situ polymerization of poly(γ-benzyl-l-glutamate) on mesoporous hydroxyapatite with high graft amounts for the direct fabrication of biodegradable cell microcarriers and their osteogenic induction. Issue 20 (9th May 2018) - Li, Linlong; Shi, Xincui; Wang, Zongliang; Wang, Yu; Jiao, Zixue; Zhang, Peibiao
Abstract : Through this method, PBLG- g -MHA microcarriers with particular properties could be prepared without any non-essential components, such as PLGA. Abstract : Large-scale cell culture for cell expansion in tissue engineering is currently a major focus of research. One method to achieve better cell amplification is to utilize microcarriers. In this study, different amounts of poly(γ-benzyl-l -glutamate) (PBLG) (from 11 wt% to 50 wt%) were grafted on mesoporous hydroxyapatite (MHA) by the in situ ring opening polymerization of γ-benzyl-l -glutamate N -carboxyanhydride (BLG-NCA), and biodegradable and biocompatible PBLG- g -MHA microcarriers were directly fabricated using the oil-in-water (O/W) solvent-evaporation technique for bone tissue engineering. The amount of grafted PBLG could be controlled by adjusting the feed ratio of MHA and BLG-NCA. The relationships between sphere morphology and graft amount or solution concentration were explored. Furthermore, cytological assays were performed to evaluate the biological properties of the PBLG- g -MHA microcarriers. For a solution concentration of 3% (w/v) and PBLG graft amounts of 33 wt% and 50 wt%, the microspheres could be harvested with optimal spherical shapes. In vitro cell culture revealed that the PBLG- g -MHA microspheres had favorable properties for cell proliferation and significantly enhanced the osteogenic differentiation of MC3T3-E1 cells and bone matrix formation.